PENUNDAAN PELAKSANAAN (SCHORSING) KEPUTUSAN TATA USAHA NEGARA PADA PUTUSAN NOMOR 74/G/2014/PTUN-BDG - Santi Hapsari Dewi Adikancana; Ladyva Rizqina Dinissa; Amanda Khoirunnisa S; Fauziyah Rahmah Izzati (Jurnal Hukum Peratun, 2022)
The Procedural Law of the State Administrative Court is a pure law which means that there is no obstacle in implementing the State Administrative Decision (KTUN) if the KTUN is sued. However, the Plaintiff can apply to postpone the disputed KTUN as compensation during the examination. The research method of this journal is normative juridical and qualitative descriptive with analytical theory. Since the issuance of the Judicial Administration Law, there have been several developments in delaying the implementation of a decision, especially in its mechanism. There are several factors that become the basis for the judge's consideration in granting a request for a postponement of the implementation of a decision, this is regulated in Article 67 of Law Number 5 of 1986, one of which is the very urgent interest of the Plaintiff. This is because the Plaintiff will suffer huge losses if the decision being sued is issued.